2012
DOI: 10.3171/2011.7.spine11222
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcome after a microsurgical unilateral approach for bilateral decompression of lumbar degenerative spondylolisthesis

Abstract: Object The aim of this study was to evaluate the results and effectiveness of bilateral decompression via a unilateral approach in the treatment of lumbar degenerative spondylolisthesis (DS). Methods Operations were performed in 84 selected patients (mean age 62.1 ± 10 years) with lumbar DS between the years 2001 and 2008. The selection criteria included lower back pain with or without sciatica, neurogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Findings in the current study are consistent with those of Pao et al and Müslüman et al, who reported no progression of spondylolisthesis following a microsurgical unilateral approach for tubular bilateral decompression after 2 years' follow-up. 39,44 The reoperation rates in our study compare favorably with those of Kim et al, who reported a 15% total reoperation rate and 7.1% reoperation rate with fusion following bilateral tubular decompressive surgery via a unilateral approach using tubular retractors. 30 Those authors concluded that decompression without fusion is more cost-effective than instrumented fusion for a selected group of patients whom they defined as those with leg-dominant pain and stable Grade I spondylolisthesis.…”
Section: Lumbar Spinal Stenosis and Spondylolisthesissupporting
confidence: 88%
See 1 more Smart Citation
“…Findings in the current study are consistent with those of Pao et al and Müslüman et al, who reported no progression of spondylolisthesis following a microsurgical unilateral approach for tubular bilateral decompression after 2 years' follow-up. 39,44 The reoperation rates in our study compare favorably with those of Kim et al, who reported a 15% total reoperation rate and 7.1% reoperation rate with fusion following bilateral tubular decompressive surgery via a unilateral approach using tubular retractors. 30 Those authors concluded that decompression without fusion is more cost-effective than instrumented fusion for a selected group of patients whom they defined as those with leg-dominant pain and stable Grade I spondylolisthesis.…”
Section: Lumbar Spinal Stenosis and Spondylolisthesissupporting
confidence: 88%
“…8,30,39,[41][42][43][44][45] In the present study we evaluated the outcome of this procedure in a larger group of patients with a longer duration of follow-up. The results were compared with those of other decompressive procedures published in the literature (Table 8).…”
Section: Minimally Invasive Decompression Of Lssmentioning
confidence: 99%
“…These results are in accordance with various studies reporting improvement in functional disability and pain after surgery for DLSS. 5,6,11,14,38,41,49,51 There were no significant differences in disability (ODI, RMDQ) or leg and back pain (VAS) between treatment groups. However, somewhat surprisingly, a significant difference was found in the percentage of patients who claimed a marked reduction in leg symptoms after surgery (e.g., pain, sensory disturbances, heavy legs, paresthesias).…”
Section: Primary Outcome Assessmentsmentioning
confidence: 97%
“…Both the bilateral interlaminar approach for bilateral decompression, 4,22,43,46,58,59,64 as well as the unilateral ap proach, 11,14,22,26,40,41,43,51,55,62 have been extensively researched and have shown promising results. Most of these studies, however, were limited by the size of the study population and choice of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…After unsuccessful medical management, a surgical intervention should be considered [5]. Several surgical techniques exist including uni-or bilateral decompression, associated or not with a posterior or circumferential fusion [6][7][8][9]. Experienced surgeons appreciate the large variability of time required for inpatient and outpatient visits and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%